1993
DOI: 10.2337/diacare.16.1.216
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Diabetes Mellitus in the Pima Indians

Abstract: The Pimas and many other American Indian populations suffer from a high incidence of diabetes and its characteristic disabling or fatal complications, and would benefit from continued research on the pathogenesis and prevention of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 49 publications
8
58
0
4
Order By: Relevance
“…This finding should be interpreted with caution because it is potentially a proxy variable for a wide range of social and cultural variables (e.g., degree of genetic risk for diabetes, degree of traditionalism, level of education, degree of discrimination experienced, acculturation stress, exposure to historical trauma, age, and fear and distrust of medical providers), some of which have been shown to affect glycemic control in other minority populations. 26,27 The degree to which these factors are interrelated may make it difficult to analyze them separately. This finding must be explored with sensitivity to the potential for misrepresentation and misuse of data regarding such variables.…”
Section: Discussionmentioning
confidence: 99%
“…This finding should be interpreted with caution because it is potentially a proxy variable for a wide range of social and cultural variables (e.g., degree of genetic risk for diabetes, degree of traditionalism, level of education, degree of discrimination experienced, acculturation stress, exposure to historical trauma, age, and fear and distrust of medical providers), some of which have been shown to affect glycemic control in other minority populations. 26,27 The degree to which these factors are interrelated may make it difficult to analyze them separately. This finding must be explored with sensitivity to the potential for misrepresentation and misuse of data regarding such variables.…”
Section: Discussionmentioning
confidence: 99%
“…It has a strong effect on the development of type 2 DM (Bjorntorp, 1992;Haffner et al, 1992) as it is found in Western countries (NDDG, 1979;Wilson et al, 1981) and some ethnic groups such as Pima Indians (Joffe et al, 1992;Knowler et al, 1993). Obesity is more than just a risk factor; it has a causal effect in the development of type 2 DM against a genetic background.…”
Section: Pathogenesis Of Type 2 Diabetesmentioning
confidence: 98%
“…Residents of the Gila River Indian Community of Arizona, most of whom are Pima or closely related Tohono O'odham Indians, participate in a longitudinal population-based study of diabetes and its complications conducted by the National Institute of Diabetes and Digestive and Kidney Diseases (7). Approximately every 2 years, each member of the community aged Ն5 years is invited to participate in a standardized examination (biennial examination) that includes a medical history, physical examination, and measurement of BMI, blood pressure, plasma glucose level, HbA 1c level, serum cholesterol concentration, and albuminuria.…”
Section: Population Study and Medical Examinationmentioning
confidence: 99%